Why SMEs Should Consider Adopting Cloud ERP: A Literature Review - Suppiah, Yogeswari; Hassan, Marina (Proceedings of the Informatics Conference, 2020)
Abstract – Technology is ever changing. On-premise ERP has been adopted by industries almost two and half decades ago. Nowadays, cloud computing has taken over the technology era. Cloud computing plays a vital role in offering an organizations with a pool of thirdparty hosting of IT resources applications and services virtually through the web. Cloud ERP also known as SaaS( Software-As-Service) ERP. Current studies show that there are many large organizations have been adopting cloud ERP recently. They have observed the benefits and opportunities offered by cloud computing. But SMEs are resistant to adopt to this new technology for various possible reasons mainly high cost of implementation. This paper aims to provide a detailed overview on the opportunities, benefits and advantages of cloud ERP. This paper would be useful for future adopters and decision makers of cloud ERP in SMEs.